Integration Internet of Things (IoT) and ChatGpt in The Teaching of Photosynthesis and Water Quality at SDN 2 Lebo - Aspin; Ikhlasul Ardi Nugroho; Abubakar; Muh Asharif Suleman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a learning model integrating the Internet of Things (IoT) and Chat Generative Pre-trained Transformer (ChatGPT) in teaching photosynthesis and water quality at SDN 2 Lebo. The research is grounded in the need to enhance early science and technology literacy, particularly in understanding abstract concepts such as photosynthesis and its environmental influences. IoT is used to monitor real-time environmental parameters—light intensity, temperature, pH, and water turbidity. ChatGPT functions as an AI-based virtual assistant providing interactive explanations of the data. The study adopts a Research and Development (R&D) method using the ADDIE model. IoT devices were developed with cloud-connected sensors, and the ChatGPT chatbot was tailored to the learning context of elementary students. Implementation involved 60 fourth- and fifth-grade students. Results showed a 32% increase in students’ understanding of photosynthesis and improved participation in scientific discussions. This research recommends the integration of IoT and AI as an innovative approach to foster critical thinking, digital literacy, and environmental awareness in primary education.